2010
DOI: 10.1096/fj.10-162156
|View full text |Cite
|
Sign up to set email alerts
|

Expression and signaling of the tyrosine kinase FGFR2b/KGFR regulates phagocytosis and melanosome uptake in human keratinocytes

Abstract: Membrane and actin cytoskeleton dynamics during phagocytosis can be triggered and amplified by the signal transduction of receptor tyrosine kinases. The epidermal keratinocytes appear to use the phagocytic mechanism of uptake to ingest melanosomes released by the melanocytes and play a pivotal role in the transfer process. We have previously demonstrated that the keratinocyte growth factor KGF/FGF7 promotes the melanosome uptake through activation of its receptor tyrosine kinase FGFR2b/KGFR. The aim of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 35 publications
(75 reference statements)
6
36
0
Order By: Relevance
“…In fact, it has been demonstrated that in keratinocytes from light skins, the autophagic activity was higher than in dark keratinocytes, inducing the rapid lysosomal-dependent degradation of melanosomes and contrasting their potentially dangerous accumulation. In agreement with these observations, results from our group have shown that FGFR2 is more expressed in light keratinocytes compared with dark ones 45 and its FGF7-dependent activation induces melanosome uptake stimulating the phagocytic process 30 , 46 . Based on these findings, our present results strongly suggest that the activation of FGF7-FGFR2 axis, through induction of melanosome autophagy, would be likely a crucial event in regulating skin color.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, it has been demonstrated that in keratinocytes from light skins, the autophagic activity was higher than in dark keratinocytes, inducing the rapid lysosomal-dependent degradation of melanosomes and contrasting their potentially dangerous accumulation. In agreement with these observations, results from our group have shown that FGFR2 is more expressed in light keratinocytes compared with dark ones 45 and its FGF7-dependent activation induces melanosome uptake stimulating the phagocytic process 30 , 46 . Based on these findings, our present results strongly suggest that the activation of FGF7-FGFR2 axis, through induction of melanosome autophagy, would be likely a crucial event in regulating skin color.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, we have recently demonstrated that the FGF7-mediated activation of FGFR2 triggers early differentiation in keratinocytes during the switch from undifferentiated to differentiating cells, 28 the same step in which it has been recently proposed that autophagy might represent a crucial event for cell commitment to differentiation 29 . Moreover, FGFR2 expression and signaling regulate the phagocytic process in keratinocytes 30 . Based on these findings, we wondered if FGF7 may modulate the autophagic process in keratinocytes.…”
Section: Introductionmentioning
confidence: 95%
“…25,51,52 In addition, unidentified surface lectins and glycoproteins are said to facilitate the transfer. 53 Epidermal melanocytes express POMC-derived peptides including adrenocorticotropin (ACTH), a-MSH and b-MSH, and b endorphins.…”
Section: Melanin Biosynthesis and Distributionmentioning
confidence: 99%
“…It is theoretically possible that keratinocytes might phagocytose Y chromosome-positive circulating blood cells, and then appear to be Y chromosome-positive themselves. Although keratinocytes have been shown to phagocytose pathogens and melanosomes [24,25], there is no evidence that they take up blood cells, and this seems unlikely to have occurred.…”
Section: Discussionmentioning
confidence: 99%